Integrating Blockchain Technology into Healthcare, A Decentralized Ledger That Improves Respect for Patients' Right to Privacy and Confidentiality - Hafiz Gulfam Ahmad Umar; Mariam Fareed; Sana Rubab; Romiza Rubab (Journal of Human Dynamics, 2024)
A patient's medical record is an essential tool for treatment and care. However, questions about privacy, interoperability, and data fragmentation have been brought to light by conventional EHR systems. The research here employs blockchain technology to safeguard the transfer and storage of patient data. Since blockchain transactions may be recorded across several computers in a decentralized manner, any future data changes will need updating each subsequent block. The study makes use of tools such as Ganache, Truffle, Metamask, ZKPs, IPFS and RemixIDE. Blockchain validation is used for patient record retrieval; this procedure generates an encrypted Content ID and a decryption symmetric key. Further assurance of privacy and security is provided by the integration of Zero-Knowledge Proofs (ZKPs), which enable users to demonstrate record access privileges without disclosing sensitive information. In addition to boosting resilience and interoperability across systems, this decentralized strategy increases the confidentiality, integrity, transparency, and access management of healthcare data. The combination of blockchain technology with zero-knowledge proofs (ZKPs) increases the reliability of healthcare transactions by safely confirming data access between nodes.
Keywords: Access control, Blockchain, Decentralization, Ethereum, Healthcare, Interoperability, patient records, Smart contracts, Solidity.